SAMSUNG, A SMOOTH OR TREACHEROUS JOURNEY OF GLOBALIZATION? - Ibeaubuchi Praisegod, Tochukwu; Ogakwu Chinedu, Uchenna; Ozeh Kingsley, Chidera; Akinnuoye Abigael, Olusola; Nwose Precious, Okwukwe (INTI International University, 2023)
This case study explores the complex and diverse journey of Samsung, the South Korean giant, as it began its process of global expansion. Samsung's transformation into a prominent worldwide technological conglomerate has been characterized by strategic ventures into various areas, continuous innovation, and skillful navigation of the obstacles inherent in the global business environment. This article analyzes the historical backdrop of Samsung's endeavors in globalizing, charting its evolution from a local contender to a significant contributor in the global technology industry. This case study examines the primary factors that propelled Samsung's globalization strategy, with a particular focus on the significance of technological innovation, market expansion, and adaptable management techniques. The case examines the company's capacity to customize items to meet local preferences while upholding a uniform global brand identity. Moreover, the study examines the influence of globalization on Samsung's organizational framework, corporate ethos, and general business approach. This case offers insights into the obstacles encountered by Samsung in various worldwide markets and the solutions implemented to overcome them. The case study emphasizes the significance of Samsung's varied range of products, robust research and development skills, and efficient supply chain management in successfully navigating the challenges of a worldwide market.